2018
DOI: 10.4049/jimmunol.1700604
|View full text |Cite
|
Sign up to set email alerts
|

GPR81, a Cell-Surface Receptor for Lactate, Regulates Intestinal Homeostasis and Protects Mice from Experimental Colitis

Abstract: At mucosal sites such as the intestine, the immune system launches robust immunity against invading pathogens while maintaining a state of tolerance to commensal flora and ingested food Ags. The molecular mechanisms underlying this phenomenon remain poorly understood. In this study, we report that signaling by GPR81, a receptor for lactate, in colonic dendritic cells and macrophages plays an important role in suppressing colonic inflammation and restoring colonic homeostasis. Genetic deletion of GPR81 in mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
109
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(119 citation statements)
references
References 59 publications
0
109
0
1
Order By: Relevance
“…Lactate is carried across cell membranes by a class of transmembrane proteins known as MCTs [also known as solute carrier 16 (SLC16)], which cotransport protons and lactate anions down the concentration gradients of the lactate anion and proton (22). MCTs constitute a family of 14 transporters, and the most common types are MCT1 (SLC16A1) and MCT4 (SLC16A3) (23).…”
Section: Monocarboxylic Acid Transporters (Mcts)mentioning
confidence: 99%
“…Lactate is carried across cell membranes by a class of transmembrane proteins known as MCTs [also known as solute carrier 16 (SLC16)], which cotransport protons and lactate anions down the concentration gradients of the lactate anion and proton (22). MCTs constitute a family of 14 transporters, and the most common types are MCT1 (SLC16A1) and MCT4 (SLC16A3) (23).…”
Section: Monocarboxylic Acid Transporters (Mcts)mentioning
confidence: 99%
“…Supplementation of lactate or pyruvate enhanced uptake and immune responses to S. typhimurium infection, which was not afforded in Gpr31 -/mice. Engagement of lactate with its other receptor, Gpr81, on intestinal dendritic cells and macrophages was also shown to reduce colitis by suppressing cytokine production and Th1/Th17 cell differentiation [84], but whether this was due to gut microbegenerated lactate in particular was not addressed.…”
Section: Effect Of Commensal Metabolites On Host Immune Functionmentioning
confidence: 99%
“…In situ hybridization showed that GPR81 is located at astrocytic end-feet membranes, endothelial cell membranes, and highly at neuronal synaptic membranes (K. H. Lauritzen et al, 2014). Furthermore, the expression of GPR81 is also found in macrophage cells (Hoque et al, 2014), uterus (A. Madaan et al, 2017), and the antigen-presenting cells (APCs) and other immune cells of the intestine (Ranganathan et al, 2018).…”
Section: The Discovery Tissue Distribution and Expression Of Gpr81mentioning
confidence: 99%